High Energy Neutrino Emission from Astrophysical Jets in the Galaxy - T. Smponias; O. T. Kosmas (Advances in High Energy Physics)
We address simulated neutrino emission originated from astrophysical jets of compact objects within the Galaxy. These neutrinos are of high energies (Eν of the order up to a few TeV) and for their observation specialized instruments are in operation, both on Earth and in orbit. Furthermore, some next generation telescopes and detector facilities are in the process of design and construction. The jet flow simulations are performed using the modern PLUTO hydrocode in its relativistic magnetohydrodynamic version. One of the main ingredients of the present work is the presence of a toroidal magnetic field that confines the jet flow and furthermore greatly affects the distribution of the high energy neutrinos.